11 Experience of COVID-19 in a hospice inpatient unit: characteristics, symptoms and ethical issues. Issue Volume 11: Issue (2021)Supplement 1 (16th March 2021) - Gardner, Emma; Tempest, Emma
Abstract : Objectives: One of the established risk factors for death from coronavirus disease 2019 (COVID-19) is comorbidity. Patients referred to palliative care before developing COVID-19 infection are therefore more vulnerable due to their pre-existing conditions. This study aimed to describe the impact of COVID-19 infection on hospice inpatients. Methods: A retrospective review was performed of patients with confirmed COVID-19 during an admission to one hospice inpatient unit in the five months between 1st March 2020 and 31st July 2020. Results: 12 patients were identified with confirmed COVID-19. Mortality during the admission was 67% (n=8). Patients had a median age of 74, were 75% male and had a median Australia-modified Karnofsky Performance Status (AKPS) of 30. 100% had comorbidities, most commonly malignancy (58%), hypertension (50%) and diabetes (50%). The symptoms most frequently recorded were confusion (67%), agitation (67%), fever (50%), cough (50%) and breathlessness (50%). Symptoms at the end of life were treated with subcutaneous infusion (100%) using commonly prescribed medications (oxycodone used in 75%, morphine 13%, midazolam 88%, levomepromazine 63%, glycopyrronium 88%, haloperidol 13%) and doses. A third of cases were detected by a routine COVID-19 swab, however this policy led to ethical debate around testing in the last days of life. Conclusions: This small case series suggests that larger studies into symptoms of COVID-19 at the end of life and their control would be helpful, particularly if they take into account baseline (and the impact on those with palliative conditions or frailty) and collect data from community settings as well as hospital care. We understand that there is heterogeneity in COVID-19 testing policies at hospices across the UK, and feel further discussion around the ethical questions raised by testing, particularly at the end of life, would be beneficial in finding our way forward in this ever-changing pandemic landscape.